Radiation of Surface Polaritons from a Charge Rotating Around a Dielectric Cylinder - Saharian, A. A.; Kotanjyan, A. S.; Mkrtchyan, A. R.; Kotanjyan, V. Kh.
We investigate the radiation of surface polaritons by a charged particle rotating around a dielectric waveguide embedded in a homogeneous medium. A formula is derived for the spectral distribution of the radiation intensity for surface-type modes. It is shown that the corresponding waves are radiated on the eigenmodes of the dielectric cylinder. The number of radiated quanta for surface polaritons of a given harmonic can be essentially larger than that for guiding modes.
Keywords: Electromagnetism; Optics